2004
DOI: 10.1111/j.1365-2621.2004.tb13379.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grinding Temperature on Hydroperoxide and Off‐flavor Contents during Soymilk Manufacturing Process

Abstract: Hydroperoxides and n-hexanal of soymilk made at different temperatures in the soybean grinding process were investigated. Both hydroperoxides and n-hexanal showed maximum amounts at 30°C, 37.78 mol/g, and 1.94 mg/g, respectively. However, at 3°C and 80°C, amounts of hydroperoxides were about half of that at 30°C. N-hexanal showed high correlation with hydroperoxides except for at 80°C. It suggests that controlling the grinding temperature is effective to reduce hydroperoxidation and off-flavor content. Protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…There were attempts to control lipoxygenase activity in soybean processing. Grinding soybean either at high or low temperatures or low pH was effective in reducing off-flavor generation (Wilkens et al, 1967;Che Man et al, 1989;Horie et al, 1999;Mizutani and Hashimoto, 2004). Rosenthal et al (2003) reported soymilk treated with Celluclast 1.5L Ò showed a substantial reduction in particle size compared to other enzymes.…”
Section: Introductionmentioning
confidence: 95%
“…There were attempts to control lipoxygenase activity in soybean processing. Grinding soybean either at high or low temperatures or low pH was effective in reducing off-flavor generation (Wilkens et al, 1967;Che Man et al, 1989;Horie et al, 1999;Mizutani and Hashimoto, 2004). Rosenthal et al (2003) reported soymilk treated with Celluclast 1.5L Ò showed a substantial reduction in particle size compared to other enzymes.…”
Section: Introductionmentioning
confidence: 95%
“…Soy protein is one of the most widely used vegetable proteins in meat industry due to its various technological benefits, whereas it plays a significant role in the modification of the functional characteristics of the meat products [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mizutani and Hashimoto [1] found that the different processing method and heating process have greatly impacted the flavor profiles of soymilk. In the current study, the results show that the boiling before filtration processing (BBF) technology produced low beany flavor than the boiling after filtration processing (BAF) technology.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Soybean food products play an important role in the current food market. Soymilk, a kind of soybean products, is abundant in protein and fatty acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation